2013
DOI: 10.4172/2168-9881.s11-003
|View full text |Cite
|
Sign up to set email alerts
|

Wide Hybridization and Embryo-Rescue for Crop Improvement in Capsicum

Abstract: Interspecific hybridization and embryo rescue in Capsicum Chilli belongs to the genus Capsicum, which is among the world's extensively grown spice crops. India ranks first with an average yield of 1.6 mt ha-1 from the total cultivated area of 7.67 lakhs ha. In Meghalaya, it is the third most important spice crops after ginger and turmeric with an area of 1900 hectares and a production of 2300 tones. However, diseases namely, Tobacco Mosaic Virus (TMV), root rot, Tomato Spotted Wilt Virus (TSWV), etc. leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
1
11
0
2
Order By: Relevance
“…Despite of low percentage of fruit set, reciprocal combinations 449×448 and 449×46 showed the highest number of seeds per fruit: 75 and 73, respectively. It is known that success in hybridization involves not only the compatibility but also pollen germination, growth of the pollen tube, fertilization, development of embryo and endosperm, and seed maturation (Debbrama et al, 2013). In this regard, in addition to the aforementioned combinations, 46×134 (73), 46×449 (64), 449×134 (63), 46×390 (62), 449×443 (61) also had a good seed number per fruit (Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…Despite of low percentage of fruit set, reciprocal combinations 449×448 and 449×46 showed the highest number of seeds per fruit: 75 and 73, respectively. It is known that success in hybridization involves not only the compatibility but also pollen germination, growth of the pollen tube, fertilization, development of embryo and endosperm, and seed maturation (Debbrama et al, 2013). In this regard, in addition to the aforementioned combinations, 46×134 (73), 46×449 (64), 449×134 (63), 46×390 (62), 449×443 (61) also had a good seed number per fruit (Table 3).…”
Section: Resultsmentioning
confidence: 94%
“…Debbarama [14] and Kharkongar [15] also reported a highly significant positive correlation between the pollen tube growth rate and pod formation percent in case of Capsicum annuum and Solanum lycopersicum, respectively.…”
Section: Pollen Tube Growth Ratementioning
confidence: 95%
“…Studies on correlation showed out that there is a significant correlation between pollen germination and percent pod formation. Debbarama [14] and Kharkongar [15] also reported a highly significant correlation between pollen germination and fruit set in Capsicum annuum and Solanum lycopersicum, respectively. Adhikari [16] reported a non-significant correlation between pollen germination and fruit set in Pisum sativum.…”
Section: Pollen Germinationmentioning
confidence: 98%
“…Sexual hybridization is an important tool to plant breeders which enables the transfer of desirable traits from one species to another [41]. The steps of sexual hybridization involve a series of events which include germination of the pollen, pollinating the maternal taxa with pollen from the paternal taxa, growth of the pollen tube, fertilization, embryo and endosperm development and seed maturation [42].…”
Section: Sexual Hybridizationmentioning
confidence: 99%